Correction to "Left uniquely generated elements in rings" [Commun. Algebra, DOI: 10.1080/00927872.2021.1908549]. Issue 9 (2nd September 2021) - Zhou, Yiqiang
Abstract: In this corrigendum, statement (5) of Proposition 4.4 is reformulated and an example is given to show that this correction is necessary.